Artificial Intelligence Applications in Education Within the Scope of the National Artificial Intelligence Strategy in Turkey - Karabatak, Songul; Ay, Sevinc; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2025)
This study examines AI-based education projects led by Turkey's Ministry of National Education. AI integration aims to enhance student achievement, optimize teaching, and support pedagogical practices. Intelligent tutoring systems, personalized learning platforms, and automated assessments provide individualized learning experiences, improving educational effectiveness. Under Turkey's 2021-2025 National AI Strategy, various initiatives focus on AI applications in teacher training, curriculum integration, and digital education platforms. Notably, the Education Informatics Network (in Turkish EBA) employs AI-powered recommendation systems to track student progress and address learning gaps. This study explores AI in education through teacher training, curriculum integration, student support, and data security. Findings suggest increasing AI adoption, yet ethical concerns, algorithmic bias, and data privacy remain critical challenges. Sustainable policy strategies are recommended to address these issues. © 2025 IEEE.
13th International Symposium on Digital Forensics and Security, ISDFS 2025 -- 24 April 2025 through 25 April 2025 -- Boston -- 209331
Keywords: artificial intelligence; artificial intelligence in education; national artificial intelligence strategy